The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4028/www.scientific.net/amm.584-586.1618
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Citrate on the Hydration Capacity of Hemihydrate Calcium Sulfate Whiskers

Abstract: The influence of sodium citrate on the hydration capacity of hemihydrate calcium sulfate whiskers was investigated. The products were characterized by FTIR, SEM and XRD.The results show that the absorption of the sodium citrate on the surface of the hemihydrate calcium sulfate whiskers is not uniform, and the adsorption state also changed with the amount of sodium citrate. Sodium citrate plays role on the hydration capacity of hemihydrate calcium sulfate whiskers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 6 publications
(4 reference statements)
1
6
0
Order By: Relevance
“…The vibration frequencies for sodium citrate are shown in Table 3. All FTIR data was interpreted using corresponding literature data [17,[22][23][24][25][26].…”
Section: Ftir Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The vibration frequencies for sodium citrate are shown in Table 3. All FTIR data was interpreted using corresponding literature data [17,[22][23][24][25][26].…”
Section: Ftir Datamentioning
confidence: 99%
“…The vibration frequencies for sodium citrate are shown in Table 3. All FTIR data was interpreted using corresponding literature data [17,[22][23][24][25][26]. Processes preventing the Al surface from reacting with water by a protective coating formed on the particle surface typically involve precipitation and adsorption.…”
Section: Ftir Datamentioning
confidence: 99%
See 1 more Smart Citation
“…13 The critical supersaturation for the growth of BaSO 4 and SrSO 4 crystals was 7.0 and 2.3, respectively, above which two-dimensional nucleation and growth occurred on the (001) plane of the two crystals. [15][16][17][18] It was reported that the conversion of α-CaSO 4 Ĵ0.5H 2 O to CaSO 4 Ĵ2H 2 O in water (20°C) was carried out via a dissolution-precipitation route because CaSO 4 Ĵ2H 2 O was more thermodynamically stable than α-CaSO 4 Ĵ0.5H 2 O at room temperature, 16 while the hydrothermal conversion (120-150°C) of CaSO 4 Ĵ2H 2 O to α-CaSO 4 Ĵ0.5H 2 O occurred via dissolution-precipitation since α-CaSO 4 Ĵ0.5H 2 O was more thermodynamically stable than CaSO 4 Ĵ2H 2 O at elevated temperature. 14 Some work has been carried out to reveal the formation mechanisms and kinetics in an aqueous system containing α-CaSO 4 Ĵ0.5H 2 O and/or CaSO 4 Ĵ2H 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…14 Some work has been carried out to reveal the formation mechanisms and kinetics in an aqueous system containing α-CaSO 4 Ĵ0.5H 2 O and/or CaSO 4 Ĵ2H 2 O. [15][16][17][18] 8,19,20 The heterogeneous nucleation of CaSO 4 Ĵ2H 2 O in the presence of sand substrates was a second-order precipitation process, 21 and the subsequent crystallization of CaSO 4 Ĵ2H 2 O in the temperature range of 15-45 °C was controlled by the surface growth with an activation energy of 15.0 kcal mol −1 . 22 Up to now little work has been done concerning the influence of supersaturation on the hydrothermal formation of α-CaSO 4 Ĵ0.5H 2 O from CaSO 4 Ĵ2H 2 O, which limited the controllable synthesis and optimization of α-CaSO 4 Ĵ0.5H 2 O whiskers.…”
Section: Introductionmentioning
confidence: 99%